115k views
19 votes
What is the answer to this Question?


8 – 6 (x – 4) = 2x – 2 (4x – 5) + 22

User MattoTodd
by
4.4k points

1 Answer

8 votes

Answer:

Here

Explanation:

Let's solve your equation step-by-step.

8−6(x−4)=2x−2(4x−5)+22

Step 1: Simplify both sides of the equation.

8−6(x−4)=2x−2(4x−5)+22

8+(−6)(x)+(−6)(−4)=2x+(−2)(4x)+(−2)(−5)+22(Distribute)

8+−6x+24=2x+−8x+10+22

(−6x)+(8+24)=(2x+−8x)+(10+22)(Combine Like Terms)

−6x+32=−6x+32

−6x+32=−6x+32

Step 2: Add 6x to both sides.

−6x+32+6x=−6x+32+6x

32=32

Step 3: Subtract 32 from both sides.

32−32=32−32

0=0

User Parameswar
by
4.7k points